2009
DOI: 10.1038/nm.1908
|View full text |Cite|
|
Sign up to set email alerts
|

A stroma-related gene signature predicts resistance to neoadjuvant chemotherapy in breast cancer

Abstract: To better understand the relationship between tumor-host interactions and the efficacy of chemotherapy, we have developed an analytical approach to quantify several biological processes observed in gene expression data sets. We tested the approach on tumor biopsies from individuals with estrogen receptor-negative breast cancer treated with chemotherapy. We report that increased stromal gene expression predicts resistance to preoperative chemotherapy with 5-fluorouracil, epirubicin and cyclophosphamide (FEC) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
459
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 570 publications
(488 citation statements)
references
References 31 publications
20
459
3
6
Order By: Relevance
“…In ER-breast cancers, gene expression patterns typical of reactive stroma predicted resistance to chemotherapy, though no link was found between this signature and outcome in untreated patients [10]. Similarly, tumor stiffness measured with ultrasound elastography predicted residual tumor burden after chemotherapy [104][105][106].…”
Section: Ecm and Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In ER-breast cancers, gene expression patterns typical of reactive stroma predicted resistance to chemotherapy, though no link was found between this signature and outcome in untreated patients [10]. Similarly, tumor stiffness measured with ultrasound elastography predicted residual tumor burden after chemotherapy [104][105][106].…”
Section: Ecm and Chemotherapymentioning
confidence: 99%
“…Recent work has linked the ECM in tumors to dormancy [9], resistance to chemotherapy or radiation [10][11][12], metastasis and metastasis tropism [13] again demonstrating the importance of understanding cell-ECM interactions. It has become apparent from both in vitro and clinical work that the ECM signals to cells through both biochemical and physical means with complex interactions between ECM composition, splicing, microstructure, and biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Farmer showed that increased stromal gene expression is predictive of resistance to chemotherapy in the setting of a randomized controlled trial. 43 …”
Section: Role Of Microenvironment In Tumor Initiation and Progressionmentioning
confidence: 99%
“…Certain breast CAFs, which are characterized by SMA expression and are referred to as PMYs, appear to play an important role in metastasis, including lymph node metastasis (3,4). Therefore, similar to the epithelial counterpart, it was hypothesized that the tumor's aggressiveness may be affected by the stromal composition, as well as the stroma's own biological properties ('stromal signature') (15,16). In the present study, we demonstrated that the stromal expression of MMP2, which is known to promote cancer invasion and metastasis by degrading various components of the extracellular matrix, varies according to the different tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%